The Selenoprotein MsrB1 Instructs Dendritic Cells to Induce T-Helper 1 Immune Responses - Lee, Ho-Jae (Antioxidants (Basel), 2020)
Immune activation associates with the intracellular generation of reactive oxygen species (ROS). To elicit effective immune responses, ROS levels must be balanced. Emerging evidence shows that ROS-mediated signal transduction can be regulated by selenoproteins such as methionine sulfoxide reductase B1 (MsrB1). However, how the selenoprotein shapes immunity remains poorly understood. Here, we demonstrated that MsrB1 plays a crucial role in the ability of dendritic cells (DCs) to provide the antigen presentation and costimulation that are needed for cluster of differentiation antigen four (CD4) T-cell priming in mice. We found that MsrB1 regulated signal transducer and activator of transcription-6 (STAT6) phosphorylation in DCs. Moreover, both in vitro and in vivo, MsrB1 potentiated the lipopolysaccharide (LPS)-induced Interleukin-12 (IL-12) production by DCs and drove T-helper 1 (Th1) differentiation after immunization. We propose that MsrB1 activates the STAT6 pathway in DCs, thereby inducing the DC maturation and IL-12 production that promotes Th1 differentiation. Additionally, we showed that MsrB1 promoted follicular helper T-cell (Tfh) differentiation when mice were immunized with sheep red blood cells. This study unveils as yet unappreciated roles of the MsrB1 selenoprotein in the innate control of adaptive immunity. Targeting MsrB1 may have therapeutic potential in terms of controlling immune reactions.